Handbook of experimental economics results - Plott, Charles R.; Smith, Vernon L. (Amsterdam New York North Holland, 2008)
Experimental methods in economics respond to circumstances that are not completely dictated by accepted theory or outstanding problems. While the field of economics makes sharp distinctions and produces precise theory, the work of experimental economics sometimes appear blurred and may produce results that vary from strong support to little or partial support of the relevant theory. At a recent conference, a question was asked about where experimental methods might be more useful than field methods. Although many cannot be answered by experimental methods, there are questions that can only
Cover -- Copyright page -- Introduction to the Series -- Preface -- Introduction -- The Book Organization -- References -- Contents of Volume 1 -- Part 1: Markets -- 1. Markets -- Part 1.1: Institutional Environments -- Part 1.2: Imperfect Competition -- Part 1.3: Dynamics of Market Adjustments -- References -- Part 2: Market Economics of Uncertainty and Information -- 2. Market Economics of Uncertainty and Information -- Chapter 35. Learning to Forecast Rationally -- 1. Introduction -- 2. The Tasks -- 3. Results -- 4. Discussion -- References -- Chapter 36. Laboratory Tests of Job Search Models -- 1. Basic Search Experiments -- 2. Precommitment/No Precommitment Experiments -- 3. Recall Experiments -- 4. Extensions of the Standard Search Model -- Acknowledgements -- References -- Chapter 37. Reciprocity and Contract Enforcement -- 1. The Contract Enforcement Problem -- 2. Experimental Design and Results of Fehr and Gèachter (1998a) -- 3. Contract Enforcement with an Imperfect Verification Technology -- 4. Summary -- References -- Chapter 38. Reciprocity in Experimental Markets -- 1. Introduction -- 2. Experimental Design -- 3. Results -- 4. Reciprocity Under Conditions of High Stakes -- 5. Related Experiments -- Acknowledgement -- References -- Chapter 39. Information Cascade Experiments -- 1. Cascades -- 2. Market Applications and Alternative Institutions -- References -- Further reading -- Chapter 40. Markets and Information Aggregation Mechanisms -- 1. Are The Lessons From The Simple Cases Useful? -- References -- Part 3: General Equilibrium and the Economics of Multiple Market Systems -- 3. General Equilibrium and Multiple Market Systems -- Chapter 41. Comparative Advantage and International Trade -- Reference -- Chapter 42. Asset Pricing -- 1. What the Theory Predicts -- 2. The Empirical Question -- 3. What the Field Data Teach Us -- 4. What the Experiments Teach Us -- References -- Chapter 43. Price Discovery and Allocation in Chains and Networks of Markets -- Reference -- Chapter 44. Multiple Market Systems and the Classical Principles of Price Dynamics in General Equilibrium -- References -- Further reading -- Part 4: Games -- 4. Games -- Part 4.1: Accuracy of the Nash Model -- Chapter 45. Experimental Beauty Contest Games: Levels of Reasoning and Convergence to Equilibrium -- Chapter 46. Reciprocity in Ultimatum and Dictator Games: An Introduction -- Chapter 47. Preferences and Property Rights in Ultimatum and Dictator Games -- Chapter 48. Prompting Strategic Reasoning Increases Other-regarding Behavior -- Chapter 49. Social Distance and Reciprocity in Dictator Games -- Chapter 50. Fairness in Ultimatum Bargaining -- Chapter 51. Coordination Failure in Market Statistic Games -- Chapter 52. The Problem of Common Choice in Symmetric N-person Coordination Games -- Chapter 53. Equilibrium Convergence in Normal Form Games -- Chapter 54. Analyzing Choice with Revealed Preference: Is Altruism Rational? -- Chapter 55. Testing Theories of Other-regarding Behavior: A Sequence of Four Laboratory Studies -- Chapter 56. Focal Points and Bargaining -- Part 4.2: Alternatives to Nash -- Chapter 57. Differences in the Economic Decisions of Men and Women: Experimental Evidence -- Chapter 58. Emergent Conventions i
This is paid thru PCED. When a dialog box appears, tick on the PCED (Philippine Center for Economic Development) from the selection.
Includes bibliographical references and index
Electronic reproduction.
Keywords: Electronic books; Economics -- Experiments -- Methodology; Economics -- Research